Social Media Use, Political Efficacy and Political Participation Among Youth During the 2016 Campaign - Stanley, Kathryn Elizabeth (East Carolina University, 2017)
This study examines social media use among youth during the 2016 election. Using an email survey administered to undergraduate students at East Carolina University, participants were asked questions about their social media use, political efficacy, and political participation. Based on the literature it was hypothesized that there will be increased political efficacy and increased political participation among youth as a result of social media use and exposure. This study found that there were some statistically significant positive associations between social media use and political participation, and social media use and political efficacy among youth.
Keywords: political SNS use